A survey on the fatty acid composition of cow’s milk in different production systems in Khorramabad, Iran with respect to ω-6:ω-3 ratio - Eskandari, Soheyl; Miyar Abbas Kiani, Salman; Kiani, Ali; Shekarchi, Maryam; Ghaffari, Farahnaz; Mohammadzadeh, Saeed; Alikami, Naghmeh (Archives of Advances in Biosciences, 2014)
The ratio of ω-6: ω-3 is connected to the higher risk of non-communicable diseases, thus this ratio is becoming more important than quantity of ω-6 and ω-3 in human nutrition. In countries like Iran, cow’s milk is mainly produced in rural area and less in conventional systems. The lactating cows reared in rural and conventional farms are different in terms of nutrition, daily yields, and proportion of concentrate to forage that these might affect milk fatty acid profiles. Therefore, the aim of this study was to determine the ratio of ω-6: ω-3 in cow’s milk produced in conventional and rural dairy farms in west of Iran, Khorramabad. Twenty bulk milk samples (rural and conventional) were collected from the conventional dairy farms and local milk collection centers. Fatty acid profiles were determined and results showed that conventional milk had higher ω-6 (2.1± 0.4) and lower ω-3 (0.16 ± 0.03) in comparison with rural milk. The ratio of ω-6:ω-3 in rural milk was significantly lower (8:1) than that in conventional milk (13:1) (p<0.01). In conclusion, milk produced in rural dairy farms had better ratio of ω-6:ω-3, thus rural milk could be healthier for human nutrition in terms of ω-3 fatty acids.